Not only climate: Interacting drivers of treeline change in Europe - Kulakowski, Dominik (2016)
Treelines have long been recognized as important ecotones and likely harbingers of climate change. However, over the last century many treelines have been affected not only by global warming, but also by the interactions of climate, forest disturbance and the consequences of abrupt demographic and economic changes. Recent research has increasingly stressed how multiple ecological, biophysical, and human factors interact to shape ecological dynamics. Here we highlight the need to consider interactions among multiple drivers to more completely understand and predict treeline dynamics in Europe.